Upaya Penciptaan Budaya Religius dilingkungan Kampus Universitas Muhammadiyah Jember - Rusdiyanto Rusdiyanto (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2019)
This study entitled " EFFORTS IN ESTABLISHING RELIGIOUS CULTURE AT THE UNIVERSITY OF MUHAMMADIYAH JEMBER. The problems were formulated as follows: 1). How religious culture at the university of Muhammadiyah Jember was conceptualized, 2). How the culture was created or established. This is a case study adopting a qualitative approach with 3 Blater as informants. Data were collected through: a) Participant observation, b) In-depth interviews. c) Documentation and literature review. This concept is then reflected in the integrative-interconnected religious curriculum applied at the University of Muhammadiyah Jember, linking one with another. Meanwhile, the concept of Islamic study in the creation of religious culture on campus environment of the university is through the implementation of learning in and outside the classroom, for example, the implementation of several activities outside the classroom is due to solid lecturers, especially AIK lecturers, with activities that include mentoring, social activities, congregational prayer, whereas in-class activities follow the standard of the curriculum of the university. In addition, strategies for establishing religious culture at the university were done through two strategies: cultural and structural. The cultural strategies include getting each individual to get used to carrying out programs or activities that are of high with Islamic values, while the structural strategies are concerned primarily with stakeholders, especially students.